Spectral inversion for ice-induced propeller moments from measurements on the propulsion shaft of a polar research vessel. (1st July 2022) - De Koker, N.
Abstract: A spectral inversion method to monitor ice-induced impact loading on the propulsion systems of vessels operating in polar waters is presented. The method adapts a continuous simulation method by representing the dynamic equilibrium of torsional loads on the shaft in the frequency domain. Shaft-line measurements are then inverted for propeller and motor torques via progressive solution of a series of low-rank linear equations. After validating the method using a benchmark ice-loading model, it is applied to operational measurements from the propulsion system of the SA Agulhas II. It is shown that the method is suitable for real-time or near real-time monitoring of loading on the propulsion system, which would provide greater situational awareness to the ice pilot, lower risk during challenging ice-navigation.